Implications Of The Unified Theory Of Acceptance And Use Of Technology 2 (Utaut2) Model On Cryptocurrency Investment Intentions Among Generation Z In Jayapura City With Financial Literacy As A Moderator - Isma Shalihi Ahlia; Musa Kris Payokwa; Aprianto La'lang Kuddy; Fanny Kristin Tantyah Sitompul; Iriando Wijaya (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the effect of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) construct on the intention to invest in cryptocurrency among Generation Z in Jayapura City, with financial literacy as a moderating variable. This study uses a quantitative approach with an explanatory method. Data were obtained from 210 respondents aged 18–30 years through probability sampling techniques. Data analysis was performed using Structural Equation Modelling–Partial Least Squares (SEM–PLS) with the assistance of SmartPLS 4.0 software. The results showed that of the eight variables tested, only financial literacy had a positive and significant effect on cryptocurrency investment intentions. Meanwhile, the seven primary constructs of UTAUT2—performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit—had no significant effect. In addition, financial literacy was found to act as a moderating variable that strengthens the influence of hedonic motivation and weakens the influence of facilitating conditions on investment intentions. These findings indicate that Generation Z's investment decisions in Jayapura are more influenced by their level of financial knowledge and readiness than by technological readiness. Theoretically, this study expands the UTAUT2 model by adding financial literacy as a relevant contextual variable in explaining digital investment behaviour in developing regions. Practically, the results of this study emphasise the importance of strengthening digital financial literacy programs for young investors, developing educational content on investment platforms, and integrating digital financial literacy into college curricula to encourage rational and sustainable investment behaviour.